2005
DOI: 10.1128/jb.187.5.1751-1762.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Control of Premature Activation of a Secreted Protease Zymogen: Deletion of Staphostatin B (SspC) in Staphylococcus aureus 8325-4 Yields a Profound Pleiotropic Phenotype

Abstract: The cytoplasmic protein SspC of Staphylococcus aureus, referred to as staphostatin B, is a very specific, tightly binding inhibitor of the secreted protease staphopain B (SspB). SspC is hypothesized to protect intracellular proteins against proteolytic damage by prematurely folded and activated staphopain B (M. Rzychon, A. Sabat, K. Kosowska, J. Potempa, and A. Dubin, Mol. Microbiol. 49:1051-1066, 2003). Here we provide evidence that elimination of intracellular staphopain B activity is indeed the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 71 publications
1
41
0
Order By: Relevance
“…These features together with a repetitive disordered segment of unknown function at the C terminus of zSspA are uniquely associated with S. aureus and one species of coagulase-negative Staphylococcus where SspA is in an operon and serves to activate an adjacently encoded cysteine protease. Others have found that expression and secretion of zSspB is toxic to S. aureus unless accompanied a third gene in the ssp operon encoding a cytoplasmic protein, SspC (Staphostatin B), that binds to and inhibits mature SspB but reportedly has no interaction with zSspB (12,14,15). Our present study has described additional safety features incorporated into the zSspA propeptide that appear to have evolved to minimize the likelihood of either protease being activated prematurely during protein export.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These features together with a repetitive disordered segment of unknown function at the C terminus of zSspA are uniquely associated with S. aureus and one species of coagulase-negative Staphylococcus where SspA is in an operon and serves to activate an adjacently encoded cysteine protease. Others have found that expression and secretion of zSspB is toxic to S. aureus unless accompanied a third gene in the ssp operon encoding a cytoplasmic protein, SspC (Staphostatin B), that binds to and inhibits mature SspB but reportedly has no interaction with zSspB (12,14,15). Our present study has described additional safety features incorporated into the zSspA propeptide that appear to have evolved to minimize the likelihood of either protease being activated prematurely during protein export.…”
Section: Discussionmentioning
confidence: 83%
“…The need for an inhibitor is supported by the finding that expression of SspB in Escherichia coli is lethal unless accompanied by Staphostatin B or a Cys 3 Ser active site mutant in SspB. Moreover inactivation of sspC in S. aureus promotes a gross disturbance in growth and protein export, supporting a role for Staphostatin B in protecting against activation of zSspB during protein export (13)(14)(15). One means by which this could occur would be if zSspA were also activated prematurely.…”
mentioning
confidence: 82%
“…It has been reported that GluV8 is processed by aureolysin, a thermolysin-family metalloprotease [6,7]. This processing was faithfully reproduced by thermolysin treatment of the recombinant proteins in vitro (Fig.…”
Section: In Vitro Processing Of the Proteases By Thermolysinmentioning
confidence: 56%
“…Drapeau [6] reported that activation of the GluV8 precursor is achieved by a neutral metalloprotease. Shaw et al [7] further demonstrated that the cascade reactions in processing of major extracellular pathogenic proteases of S. aureus from metalloprotease/aureolysin, GluV8/SspA, and finally, to cysteine protease/SspB. We previously purified [8] and cloned [9] the glutamyl endopeptidase from Staphylococcus epidermidis (designated GluSE), which consists of 282 amino acids composed of a preprosequence (Met 1 -Ser 66 ) and mature portion (Val 67 -Gln 282 ).…”
Section: Introductionmentioning
confidence: 99%
“…While no cases of bacterial resistance to lysins have been reported as yet, four mechanisms inducing resistance to lysostaphin have been identifi ed (Shaw et al 2005 ;Gr ü ndling et al 2006 ;Kusuma et al 2007 ). These are described in more detail in Chapter 7 .…”
Section: Resistancementioning
confidence: 99%